Africa’s Rapid Population Growth and Migratory Pressures - (:unkn) unknown (My University, 2016)
Rapid population growth in Africa, and especially in Sub-Saharan Africa, will fuel migratory movements toward Europe. Migration push factors will be aggravated by the poor governance that continues to plague many African states.
Keywords: African Research